ADVERSITY QUOTIENT DENGAN PROKRASTINASI AKADEMIK MENYELESAIKAN SKRIPSI PADA MAHASISWA PSIKOLOGI UKSW - Mise Chordias Br Ginting; Christiana Hari Soetjiningsih (Jurnal Cakrawala Ilmiah, 2023)
This research was intentded to know the difference relationship between Adversity Quotient and academic procrastination in completing thesis for students of the Faculty of Psychology, Satya Wacana Christian University. The participants in this study were 55 psychology students from class 2017. The method used in this research is quantitative correlation. Data collection was carried out using a modified procrastination measurement tool from the Tuckman Procrastination Scale (TPS) and an adversity quotient scale modified by the Adversity Response Profile (ARP). The data analysis technique used in this study is the product moment correlation analysis technique. The results of this study show that there is a significant negative relationship between the Adversity Quotient and academic procrastination. This can be seen from the value of the correlation coefficient r = -0.378 with sig = 0.002 (p <0.05). Which means the higher the adversity quotient, the lower the academic procrastination, and conversely the lower the adversity quotient, the higher the academic procrastination.